EFFECT OF DIFFERENT GROWTH REGULATORS ON TORS ON TORS ON IN VITRO MICROTUBERIZATION OF TION OF TION OF SOLANUM TUBEROSUM - P. MOHAPATRA, PRIYADARSHANI; SUBHASH KAJLA, V. K BATRA; POONIA, ANIL K. (The Bioscan, 2016)
An efficient protocol has been developed for microtuberization in potato cv. Kufri Frysona, world’s most important tuber crop. Nodal segments from in vitro established multiplied shoots were inoculated on MS basal medium supplemented with different combinations and concentrations of cytokines, auxins and sugar. Maximum number of microtubers (2.5) were obtained on medium PTM3 (MS basal salt + 0.01mg/l BAP+0.01mg/ lNAA+0.1mg/lGA3+Sugar 80g/l) in 52.3 days with maximum 9.0 mm size and 0.27 g weight .Maximum percent survival rate (60%) of microtubers was obtained under field conditions.